2008
DOI: 10.3418/jjam.22.180
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and sleepiness characteristics in first trimester expectant mothers

Abstract: PurposeBecause sleep is essential for normal pregnancy-associated physiological changes and healthy fetal development it is important to provide advice to first trimester expectant mothers in order to enhance self-care. Therefore, the aims of the present study are to clarify first trimester sleep quality and sleepiness characteristics, and to elucidate the affects of stress on sleep and sleepiness characteristics. MethodsSelf-administered questionnaires were distributed to 46 first trimester expectant mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Pregnant women's sleepiness has not been emphasized as an abnormal sign, assuming that it may be related to physical changes such as the secretion of pregnancy-associated hormones and an increase in the uterine capacity. However, several studies showed that a sleep time of 6 hours or less for pregnant women prolonged the duration of birth, increasing the rate at which cesarean birth (CB) was selected (Suzuki, Ohida, Sone, et al, 2003 ;Shinkawa , Shimada, Fujita, 2008 ;Lee & Gay, 2004), suggesting an association between sleep and the outcome of birth.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women's sleepiness has not been emphasized as an abnormal sign, assuming that it may be related to physical changes such as the secretion of pregnancy-associated hormones and an increase in the uterine capacity. However, several studies showed that a sleep time of 6 hours or less for pregnant women prolonged the duration of birth, increasing the rate at which cesarean birth (CB) was selected (Suzuki, Ohida, Sone, et al, 2003 ;Shinkawa , Shimada, Fujita, 2008 ;Lee & Gay, 2004), suggesting an association between sleep and the outcome of birth.…”
Section: Introductionmentioning
confidence: 99%
“…However, nap hours were not counted in the PSQI-J towards the sleep duration. It is reported that sleepiness during the day is highly prevalent in the first trimester [40], and daytime dysfunction is believed to be common, although sleep duration at night is considered appropriate [19]. Our data might be biased given the lack of data on nap duration.…”
Section: Discussionmentioning
confidence: 89%